Bioengineering of fungal endophytes through the CRISPR/Cas9 system - Verma, Vinita; Batta, Arpita; Singh, Harikesh B.; Srivastava, Alok; Garg, Sanjay Kumar; Singh, Vijay Pal; Arora, Pankaj Kumar (Frontiers in Microbiology, 2023)
Fungal endophytes are the vital source of biologically active compounds, which possess excellent properties in clinical and industrial point of view. However, these fungal species create a complex network with their host plant, which influences the production of these bioactive compounds. Fortunately, CRISPR (Clustered Regularly Interspaced Palindromic Repeats) has been emerged as an advance and magnificent technique for genetic engineering in fungal endophytes. CRISPR/Cas9 system plays a significant role in disrupting or inserting target genes/clusters in fungal endophytes as discussed in the review. Moreover, we have also considered the implementation of CRISPR/Cas9 can be beneficial to single as well as dual loci gene manipulation in order to enhance the potential of fungal endophytes for producing relatively high content of desired and novel bioactive compounds. However, a few data has been reported regarding the application of CRISPR/Cas9 gene editing technology in the study of fungal endophytes. Hence, present review highlights the advantages of using the precise CRISPR/Cas9 gene-editing tool, which will further help researchers to investigate fungal endophytes and associated potent bioactive compounds in depth. This is the first review on application of CRISPR/Cas9 in engineering of fungal endophytes.